An Evaluation of the Scattering Law for Light and Heavy Water in ENDF-6 Format, Based on Experimental Data and Molecular Dynamics - Marquez Damian, Jose Ignacio; Granada, Jose Rolando; Malaspina, David Cesar (Elsevier Science, 2014)
Fil: Marquez Damian, Jose Ignacio. Comisión Nacional de Energía Atómica. Centro Atómico Bariloche; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina